CAR T-cell therapy for multiple myeloma CAR-T-Zell-Therapie beim multiplen Myelom - Zhou, Xiang; Einsele, H.; Danhof, S. (Internist, 2021)
Chimeric antigen receptor (CAR) T-cell treatment is a novel immunotherapy utilizing the patientʼs own immune system as a “weapon against tumor cells”. In patients with multiple myeloma (MM), CAR T-cell therapy has been investigated in clinical trials. The current data on B‑cell maturation antigen (BCMA)-targeted CAR T-cells have shown impressive efficacy, and official approval is expected shortly. However, the majority of patients relapse after CAR T-cell therapy. Moreover, the treatment can cause severe adverse events such as cytokine release syndrome and neurotoxicity with lethal outcome. The cost–benefit ratio of this treatment also needs to be optimized. Despite these limitations, CAR T-cell therapy represents an attractive option for patients with MM and has the potential to be incorporated into the standard of care.
CRIS-Team Scopus Importer:2023-03-23
Keywords: B‑cell maturation antigen; CAR T‑cell therapy/adverse events; Immunotherapy; adoptive; Receptors; chimeric antigen; T‑lymphocytes